Creep-age forming of AA7475 aluminum panels for aircraft lower wing skin application - Inforzato, Diego José (2012)
Creep-age forming (CAF) is an interesting process for the airframe industry, as it is able to form or shape panels into smooth, but complex, curvatures. In the CAF process, the ageing cycle of the alloy is used to relax external loads imposed to the part, through creep mechanisms. Those relaxed stresses impose a new curvature to the part. At the end of the process, significant spring back (sometimes about 70%) is observed and the success in achieving the desired form depends on how the spring back can be predicted in order to compensate it by tooling changes. Most of the applications relate to simple (non stiffened) panels. The present work deals with the CAF of aluminum panels for aircraft wing skin application. CAF was performed using vacuum-bagging autoclave technique in small scale complex shape stiffened panels, machined from an AA7475 alloy plate. An analytical reference model from the literature was employed estimate the spring back effect in such panel geometry. This model that deals with simple plates was adapted to stiffened panels using a geometric simplification, resulting in a semi-empirical model. The results demonstrate that CAF is a promising process to form stiffened panels, and the spring back can be roughly estimated through a simple model and few experiments.